Pop Art & Cie 1960 - 1970 - Pluchart, François (Paris : Editions Martin-Malburet, 1971)
Acconci, Vito ; Andre, Carl ; Ben ; Beuys, Joseph ; César ; Christo ; Duchamp, Marcel ; Johns, Jasper ; Judd, Donald ; Klein, Yves ; Malevitch, Kasimir ; Manzoni, Piero ; Rauschenberg, Robert ; Warhol, Andy ; etc.
Frans
boek